2021
DOI: 10.1038/s41598-021-91012-w
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gene set signatures correlates with response to nivolumab in platinum-resistant ovarian cancer

Abstract: Based on our previous phase II clinical trial of anti-programmed death-1 (PD-1) antibody nivolumab for platinum-resistant ovarian cancer (n = 19, UMIN000005714), we aimed to identify the biomarkers predictive of response. Tumor gene expression was evaluated by proliferative, mesenchymal, differentiated, and immunoreactive gene signatures derived from high-grade serous carcinomas and a signature established prior for ovarian clear cell carcinoma. Resulting signature scores were statistically assessed with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Although the conclusions that can be drawn are limited by the small cohort, our data support other clinical and pre-clinical studies that have shown the potential role of ARID1A and HER2 alterations, as well as a clear cell carcinoma-specific gene signature, as biomarkers of response to immune checkpoint blockade. [17][18][19][20][21][22] Interestingly, the patient with a germline monoallelic PMS2 mutation had preserved PMS2 immunohistochemistry and low tumor mutation burden, suggesting the tumor was not driven by mismatch repair alteration.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%
“…Although the conclusions that can be drawn are limited by the small cohort, our data support other clinical and pre-clinical studies that have shown the potential role of ARID1A and HER2 alterations, as well as a clear cell carcinoma-specific gene signature, as biomarkers of response to immune checkpoint blockade. [17][18][19][20][21][22] Interestingly, the patient with a germline monoallelic PMS2 mutation had preserved PMS2 immunohistochemistry and low tumor mutation burden, suggesting the tumor was not driven by mismatch repair alteration.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%